PHYLOGENETIC BIOGEOGRAPHY OF THE FAMILY MONIMIACEAE - A. V. Bobrov; A. A. Iurmanov; D. H. Lorence (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2017)
A complex cladistic analysis of molecular and morphological data of the Monimiaceae family is carried out. The hypothetic modes of the family dispersal are reconstructed basing on the data received for the studied representatives of the Monimiaceae family from all parts of the range and available fossils data. The family supposedly originated in Africa and penetrated into South America via the Antarctic way, and through the Arabian Peninsula and Sri-Lanka to South-Eastern Asia, Australia, New Zealand, New Caledonia, and further then to Madagascar.